Party Switching in Israel A Historical and Comparative Analysis. - Nikolenyi, Csaba (Princeton : State University of New York Press, 2023)
Analyzes the history of legislative party switching and its regulation in the Israeli Knesset.
Chapter 8 Comparative Cases: Anti-Defections Laws and Their Consequences in India, New Zealand, and South Africa -- The Growing Severity of the Anti-Defection Law in India, 1985-2003 -- Electoral Integrity Legislation in New Zealand -- Anti-Defection Law in a New Democracy: South Africa -- Conclusion -- Conclusion -- Party Switching, Anti-Defection Laws, and the Political Instability of 2019-2021 -- In Closing . . . -- Appendix -- The List of Party Switches in the Knesset, 1949-2019 -- First Knesset -- Second Knesset -- Fifth Knesset -- Sixth Knesset -- Seventh Knesset -- Eighth Knesset
Description based upon print version of record.
Ninth Knesset
JSTOR
Keywords: Israel. -- Keneset -- Rules and practice; Israel. -- Keneset; Party affiliation -- Israel; Political parties -- Israel; Political candidates -- Israel; Partis politiques -- Adhésion -- Israël.; Candidats (Élections) -- Israël.; POLITICAL SCIENCE / Comparative Politics; Party affiliation; Political candidates; Political parties; Israel; Rules